ESOPHAGEAL CANCER INCIDENCE IN TOMSK REGION - L. F. Pisareva; I. N. Odintsova; О. А. Ananina; S. G. Afanasyev; М. Yu. Volkov; N. P. Lyakhova (Сибирский онкологический журнал)
During the period 2008–2011, esophageal cancer comprised 2,5 ± 0,2 % of all cases for males and 0,5 ± 0,1 % for females. Despite worldwide tendency towards decreased incidence of esophageal cancer, the rise in the age-standardized incidence rate was observed for both males and females of Tomsk region from 2000 to 2011. For males, the increase in both crude and age-standardized rates was registered. For females, the same tendency was observed in patients in the 50 to 64 age group.